378 Awardee Talk - Impact of fetal versus maternal contributions of Bos indicus and Bos taurus genetics on embryonic and fetal development. (5th December 2019) - Fontes, Pedro Levy Piza; Oosthuizen, Nicola; Ciriaco, Francine M; Sanford, Carla D; Canal, Luara Bertelli; Pohler, Ky; Henry, Darren D; Mercadante, Vitor R G; Timlin, Claire; Ealy, Alan; Johnson, Sally; DiLorenzo, Nicolas; et al.
Abstract: To evaluate how the inclusion of Bos indicus genotype influences early fetal development in cattle, a reciprocal embryo transfer approach was used in a completely randomized design with a 2×2×2 factorial arrangement of treatments in order to generate 55 pregnancies (n = 55). Recipient cows were randomly assigned to 1) a diet that met daily energy maintenance requirements (MAINT), or 2) a diet that restricted intake to 70% of the energy maintenance requirements (RESTR). Angus (AN) and Brangus (BN) embryo donors were superovulated and artificially inseminated with female sexed-sorted semen from the same breed. Embryos were then randomly transferred to either AN or BN recipients fed their respective diets for 28d. Recipients remained on the dietary scheme until d91 of gestation, and were then comingled and fed a common diet that met their requirements. Measurements included pregnancy establishment at d28 of gestation, pregnancy-associated glycoproteins (PAG; using 2 commercial [A1 and A2] and 1 in-house assay), and fetal size (CRL). Recipients in the RESTR diet had lower BW and BCS (diet×day; P < 0.01) than MAINT recipients. Energy-restricted AN recipients experienced greater (recipient breed×diet, P < 0.01) pregnancy failure by d28 than the other recipient breed × diet combinations. Restricted recipients that received AN embryos experienced greater pregnancy failure than RESTR recipients receiving BN embryos (embryo breed×diet; P = 0.03). Brangus embryos resulted in greater plasma concentrations of PAG in both A1 (embryo breed×day, P < 0.01) and A2 (embryo breed P < 0.01). Alternatively, recipients that received AN embryos had greater plasma concentrations of PAG for the in-house assay (embryo breed×day; P < 0.01). In addition, fetuses from AN recipients had greater CRL on d91 (breed×day, P < 0.01). In summary, Bos taurus cows experienced greater pregnancy failure when nutrient restricted. Furthermore, fetal size and profile of PAG production during early gestation differed between Bos indicus-influenced and Bos taurus cattle.